Establishment of “Retinoblastoma center” in A Tertiary Eye Care Center of Bangladesh – A New Hope for Retinoblastoma Patients - Rani Roy, Soma (BOHR International Journal of Current Research in Optometry and Ophthalmology, 2022)
Retinoblastoma is the most common primary intraocular tumor in children with an incidence of 1:16,000 to 18,000 live birth. Worldwide newly detected cases per year are about 8000 and in India above 1400. It represents 11% of cancer that develops in the first year of life. The revolutionary management strategy has increased the survival rate of retinoblastoma above 95% in developed countries, and this rate is the highest among all pediatric cancers. But still, it is deadly cancer worldwide. Survival from retinoblastoma based on income >90% vs. 40% (in high to low-income countries). The incidence of metastasis is more in lower-income countries (32% vs. 12% in middle-income). Notably, Forty-three percent of the world’s estimated cases reside in only 6 countries in Asia (China, Indonesia, Philippines, India, Pakistan, and Bangladesh). The mortality rate varies on different continents. Worldwide estimated death from retinoblastoma is more than 40%, and most of them are from Asia and Africa. Bangladesh is one of the developing countries in the South-East Asia region, and retinoblastoma constitutes 83% of all pediatric cancer under 4 years of age. For proper management of retinoblastoma with an international standard, the establishment of a retinoblastoma center consisting of ocular oncologist, clinical oncologist, radiation oncologist, pediatrician, oculoplastic surgeon, retina specialist, pediatric ophthalmologist, and ocularist is needed. Management includes proper diagnosis, treatment of the disease, genetic counseling, regular follow-up, rehabilitation of survivors, and screening of siblings. Chittagong Eye Infirmary & Training Complex is a tertiary eye care center and one of the referral centers of Bangladesh and is treating retinoblastoma since its inception. Due to the demand of time, the hospital has been reorganized with various facilities to serve retinoblastoma patients with a team approach in 2017. From January 2017 to March 2022, a total of 304 patients were diagnosed. Among them, 132 received vincristine, etoposide, and carboplatin (VEC) chemotherapy from this center, and 79 underwent enucleation with the long optic nerve. Besides treatment, the hospital is conducting sibling screening, visual and psycho-social rehabilitation for the RB survivors, and community awareness programs.